Development and Validation of an Indian Nutrition and Food Literacy Tool (INFOLIT) for adolescents - Yadav, Simran; Konapur, Archana; Mokalla, Thirupathi Reddy; Gavaravarapu, SubbaRao M. (Frontiers in Nutrition, 2025)
BackgroundNutrition and food literacy (NFL) are interconnected yet distinct concepts concerning the capability to comprehend and utilize knowledge pertaining to nutrition and food. NFL is a significant driver that shapes an individuals’ diet. This is more so among adolescents whose dietary choices leave a lasting impact on nutritional and health outcomes in adulthood. Assessing NFL can help design tailored interventions to empower adolescents to make informed dietary decision. However, there is lack of standardized tools to assess NFL among adolescents, especially in India.ObjectiveTo develop and validate an Indian Nutrition and Food Literacy Tool (INFOLIT) for adolescents with a focus on key literacy domains.Materials and methodsThis five-phased cross-sectional sequential exploratory study was conducted among adolescents (13–15y) in Hyderabad, Telangana. In Phase-1, an item-pool was created for tool development through literature review and it was tested for content validity in phase-2 by experts (n = 5) using a Content Validity Index (CVI) and Cognitive Interviews (CIs) with adolescents (n = 15). In phase-3, Psychometric tests (Cronbach’s α, item and factor analysis) were performed among 400 adolescents. In phase-4, reliability was assessed (n = 30) using the Intra-class Correlation Coefficient (ICC) and Bland–Altman plot was tested and in Phase-5, the tool was graded using tertile-based stratification.ResultsThe initial item pool included 98 items into two domains - Cognitive and Skill-based for creating framework. The cognitive-domain had one dimension- Knowledge; whereas, the skill-domain had three dimensions-(i)functional, (ii)interactive and (iii)critical. Content validity and cognitive interviews eliminated 13 items. The item difficulty (p) and item discrimination (D) indices ranged 0.10–0.98 and 0.00–0.88, respectively, with strong internal consistency (Cronbach’s α = 0.81). Due to sample size limitations, factor analysis was used only for item reduction. These steps further reduced 12 items, resulting in a 73-item pool. The ICC was 0.895, and Bland–Altman plots revealed negligible mean biases indicating good reliability. The scores were categorized as low (≤40), medium (41–55), and high (≥56) out of 73.ConclusionThe INFOLIT is a validated and culturally relevant tool for assessing adolescent NFL and can be adapted for use in various Indian regions and contexts after minor modifications.